Evaluation of tigernut (cyperus esculentus l., brown variety) flour in the production of wheat-tigernut composite biscuit - Elleason, Gifty (2016)
A thesis submitted to the Department Of Food Science And Technology, in partial fulfilment for the award of the degree OF (Master of Science in Food Science and Technology), 2015